1991
DOI: 10.1148/radiology.181.2.1924804
|View full text |Cite
|
Sign up to set email alerts
|

CT patterns of intracranial hemorrhage complicating thrombolytic therapy for acute myocardial infarction.

Abstract: Computed tomographic (CT) patterns of intracranial hemorrhage (ICH) were determined in 1,696 patients undergoing thrombolytic therapy for acute myocardial infarction. ICH occurred at 33 sites in 0.77% of patients (n = 13). Thirty-six percent of hemorrhages (n = 12) were intraparenchymal, 33% (n = 11) were subdural, 24% (n = 8) were subarachnoid, and 6% (n = 2) were intraventricular. Eight-four percent (n = 26) of all nonventricular hemorrhages were supratentorial in location. The most common site of ICH was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Although the relationship of head trauma to SDH pathogenesis is well established, 13,34 the association observed in this study reinforces that any prior traumatic vascular lesion, even if clinically asymptomatic, is a risk factor for developing this high-volume, high-mortality lesion. This conclusion is cautiously made, however, since there is no way to account for whether bias in history taking existed for this subgroup.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although the relationship of head trauma to SDH pathogenesis is well established, 13,34 the association observed in this study reinforces that any prior traumatic vascular lesion, even if clinically asymptomatic, is a risk factor for developing this high-volume, high-mortality lesion. This conclusion is cautiously made, however, since there is no way to account for whether bias in history taking existed for this subgroup.…”
Section: Discussionsupporting
confidence: 61%
“…5,[13][14][15] Age, hypertension, low body weight, and elevated fibrin degradation products have been identified as clinical risk factors, and amyloid angiopathy, hypertensive vascular disease, and hemorrhagic transformation of a prior silent cerebral infarct have been reported as underlying neuropathologic causes. [15][16][17][18][19] The studies from which these reports are based, however, are seriously limited by small case series, lack of consistent clinical or neuroimaging documentation of cerebrovascular complications, and uncommon use of more than one thrombolytic regimen.…”
mentioning
confidence: 99%
“…ICH complications result in a high mortality rate, high financial costs, and a worse quality of life for surviving patients. The incidence of ICH ranges from the 0.22% noted in the GISSI study (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) to 1.4% (16).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the results of this study in relation to age are similar to those obtained in most previous studies. Hypertension is a classic complication associated with the occurrence of ICH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence of aneurysmal rupture as an adverse event of thrombolysis in ischemic stroke is unknown. Estimates of intracranial hemorrhages in terms of subarachnoid hemorrhage, possibly due to aneurysmal bleeding, or parenchymal hemorrhage are not available from stroke trials [3,4,9], but one review on thrombolysis in myocardial infarction revealed a subarachnoid hemorrhage in 24 % of those cases with intracranial bleedings [10].…”
mentioning
confidence: 99%